2021
DOI: 10.1016/j.clnu.2021.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Associations of circulating insulin-like growth factor-I with intake of dietary proteins and other macronutrients

Abstract: Background & aims: Circulating insulin-like growth factor-I (IGF-I) is associated with the risk of several cancers. Dietary protein intake, particularly dairy protein, may increase circulating IGF-I; however, associations with different protein sources, other macronutrients, and fibre are inconclusive. Aim: To investigate the associations between intake of protein, macronutrients and their sources, fibre, and alcohol with serum IGF-I concentrations. Methods: A total of 11,815 participants from UK Biobank who c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 44 publications
(58 reference statements)
1
20
0
Order By: Relevance
“…Because nutrition is perhaps the most relevant modulator of IGF‐1 levels (Key, 2011 ; Levine et al, 2014 ; Watling et al, 2021 ), third national health and nutrition examination survey (NHANES III, 1988–1994) data were used to investigate the relationship between IGF‐1 and the daily intake of specific nutrients. The study population included 1152 men and 1453 women.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because nutrition is perhaps the most relevant modulator of IGF‐1 levels (Key, 2011 ; Levine et al, 2014 ; Watling et al, 2021 ), third national health and nutrition examination survey (NHANES III, 1988–1994) data were used to investigate the relationship between IGF‐1 and the daily intake of specific nutrients. The study population included 1152 men and 1453 women.…”
Section: Resultsmentioning
confidence: 99%
“…*For both Friedrich' studies IGF-1 cutoffs were computed as mean values of the groups identified according to the age-and sex-specific 10th and 90th percentile. (d, e) Forest plot of pooled analysis for the low (d) and the high (e) categories of IGF-1 compared to the middle category (hazard ratios reported in the log scale in both panels)2.6 | Epidemiological diet studyBecause nutrition is perhaps the most relevant modulator of IGF-1 levels(Key, 2011;Levine et al, 2014;Watling et al, 2021), third national health and nutrition examination survey(NHANES III, 1988-1994 data were used to investigate the relationship between IGF-1 and the daily intake of specific nutrients. The study population included 1152 men and 1453 women.…”
mentioning
confidence: 99%
“…To date, no established dietary risk factor has been found in relation to prostate cancer risk, although there is some evidence which suggests that higher intake of dairy products, and possibly milk specifically, may increase the risk of prostate cancer [48]. This association has been proposed to be possibly mediated through IGF-I [22,49], a hormone shown to be positively associated with both milk intake and prostate cancer risk [25,50]. In this cohort, slightly lower IGF-I concentrations have been observed in vegetarians compared to regular meat-eaters [21], and IGF-I has also been associated with prostate cancer risk [25]; however, the difference in IGF-I concentrations between these diet groups is small and may not confer a substantial difference in prostate cancer risk.…”
Section: Prostate Cancermentioning
confidence: 99%
“…Due to its main functions in growth, IGF-1, as well as growth hormone (GH), nutrients are an important part of its signaling transduction regulation. In this sense, clinical and experimental studies have shown that intake of protein (especially from milk and yogurt), fibre, starch from wholegrains, redmeats, fats and oils are positively associated with IGF-1 serum levels (19)(20)(21). The disparity of one or more nutrients could affect growth, anabolism and nutrient sensing.…”
Section: Energy-dense (High Intake Of Sugars and Saturated Fatty Acid...mentioning
confidence: 99%